Filosofia e Religione: insieme salveranno l’uomo e la società - Aguilar LC, Alfonso (Alpha Omega, 2010)
Both philosophy and religion intend to offer truth and happiness to man. Although their main objective is the same, philosophy and religion use different principles, goals and methods, because each of them appeals to a different dimension of man and society. When philosophy and religion fight one other as if they were in competition, society ends up being totalitarian, either by becoming theocratic or confessional (when religion destroys reason) or secularist (when reason destroys religion). Such a cultural war is unnecessary and artificial. Man and society are by nature, at the same time, philosophical and religious, secular and spiritual. We cannot philosophize without a belief or believe without reasoning. Man and society, therefore, should not choose between faith and reason. The right choice is for both faith and reason. On the one hand, religion enhances philosophy by purifying it from hybris, by offering it new horizons and by giving it clearer signs not to go astray from the truth. On the other hand, philosophy enhances religion by purifying it from any type of irrational fideism, by offering it rational categories to understand its dogmas, and by making it reasonable to the point of making it capable of appealing to all men and women. A society flourishes in the degree it is built upon the solid rock of a healthy secularity, where the temporal and spiritual realms, philosophy and religion, the State and the Church, are respected in their relative autonomy, thus allowing each of them to offer its own specific and irreplaceable contribution to the common good. For this reason, philosophy and religion can together save man and mankind.